PEDAGOGICAL PROFESSIONAL COMPETENCE AND ITS ESSENCE - Chuponkulova Sitora Bazarovna (Journals Park Publishing, 2022)
It is a very important situation to comment on the concept of pedagogical skill, scientific ideas of scientists on pedagogical skill, criteria of pedagogical skill. held. Pedagogical aspects of the formation of pedagogical skills in preschool educators are also explained. The article talks about pedagogical professional competence and its essence.
Keywords: pedagogical competence, professional competence, essence, pedagogical skills, communication